National Stereotypes and Robots' Perception: The “Made in” Effect - Spatola, Nicolas; Anier, Nolwenn; Redersdorff, Sandrine; Ferrand, Ludovic; Belletier, Clément; Normand, Alice; Huguet, Pascal (Frontiers in Robotics and AI, 2019)
In the near future, the human social environment worldwide might be populated by humanoid robots. The way we perceive these new social agents could depend on basic social psychological processes such as social categorization. Recent results indicate that humans can make use of social stereotypes when faced with robots based on their characterization as “male” or “female” and a perception of their group membership. However, the question of the application of nationality-based stereotypes to robots has not yet been studied. Given that humans attribute different levels of warmth and competence (the two universal dimensions of social perception) to individuals based in part on their nationality, we hypothesized that the way robots are perceived differs depending on their country of origin. In this study, participants had to evaluate four robots differing in their anthropomorphic shape. For each participant, these robots were presented as coming from one of four different countries selected for their level of perceived warmth and competence. Each robot was evaluated on their anthropomorphic and human traits. As expected, the country of origin's warmth and competence level biased the perception of robots in terms of the attribution of social and human traits. Our findings also indicated that these effects differed according to the extent to which the robots were anthropomorphically shaped. We discuss these results in relation to the way in which social constructs are applied to robots.